THE EFFECT OF MARKETING MIX ON PURCHASE DECISIONS AT MIXUE : CASE STUDY OF MIXUE MOJOKERTO OUTLET - Widyaswari, Farah Adelia; Winarno, Sri Tjondro; Roidah, Ida Syamsu (Yayasan Education and Social Center, 2024)
There is a phenomenon of massive expansion by Mixue in Indonesia. The Mixue company has proven to be aggressive in expanding new outlets in Indonesia. According to one expert in marketing strategy, the mixue-ization phenomenon occurred because Mixue succeeded in applying the concepts of marketing strategy appropriately. In this case, Mixue succeeded in using the four marketing mix variables namely price, product, place, and promotion well. However, along with its development to dominate the market share quite rapidly, Mixue now looks only crowded for a moment and many outlets are threatened with closure.This study was conducted with the aim of analyzing the effect of marketing mix 7P on purchase decisions at Mixue Mojokerto Outlet. The data analysis used in this study used SEM-PLS analysis with the WarpPLS approach. The use of the PLS method as an analysis technique has the advantage that the sample used does not have to be large and can be used in developing a theory. The sample used amounted to 50 respondents who were consumers with more than 17 years of age with minimum one time purchasing at Mixue Mojokerto Outlet. The sampling employed nonprobability with a purposive sampling technique. The results of this study indicate that product, price, place, promotion, people, process and physical evidence has a positive and significant effect on purchase decision at Mixue Mojokerto Outlet